Structure and reactivity of ß-enaminones - Šimůnek, Petr (Univerzita Pardubice, 2002)
The structure of ß-enaminones is discussed from three points of view: distribution of electron density and related reactivity towards electrophiles, geometrical isomerism and tautomerism. Geometrical isomerism and tautomerism are discussed from various aspects.
Keywords: ß-enaminy; struktura; reaktivita; vlastnosti látek; tautomerie; izomerie